Instrumented childbirth - obstetric surgery - Cabero Roura, Luis (2015)
Cesarean section on demand: a growing myth. Strategies to reduce the number of cesareans. Prevention of vertical transmission (HIV): new technique of caesarean section. Role of perinatology tococirugía. Vaginal birth after cesarean. Safe surgery checklist.